TRACES OF PARODIC ELEMENTS IN THE SELECT NOVELS OF ORHAN PAMUK (International Journal of Food and Nutritional Sciences, 2022)
The idea of identity-swapping is found more than once in the novels of Orhan Pamuk, which made the researcher interested in getting into the probable reasons why the writer has incorporated such ideas repeatedly. Three of Pamuk’s novels have been taken for this study, wherein the researcher has tried to look at them in the light of postmodernism. Parody, one of the metafictional elements, is found to be an important reason behind this swapping of identities.